Indices de productions au sein d’une communauté religieuse carolingienne : l’exemple de Cysoing (Nord) - Damien Censier; Emmanuelle Bonnaire; Cécile Bouet; Renaud Leroy; Héloïse Esteves; Étienne Louis (Archéologie Médiévale)
The site “Le Clos de l’Abbaye” in Cysoing is a monastic place dedicated to saint Calixte and founded around 850 A.D. by Gisele and Évrard de Frioul. The plot of around 5,000 m², seems to be localized on the outbuildings of the religious center of the Early Middle Ages. The site is characterized by a ditch surrounding an installation made up of more than 150 pits diggings or layers. The study of the environmental data testifies to farming methods as well as cattle husbandry. Groups of silos, oven, pits, post-holes, sunken huts illustrate a intense activity. The transformation of primary products (cereal, wool, bone, metals) into finished or semi-finished products (bread, textile, clothing, jewelry) is revealed by various archaeological facts or artefacts. A small amount of ceramics, allows to date the site and to see a network of supplies